The human brain prenatal development and structure - Marín-Padilla, Miguel (Springer, 2011)
This book is unique among the current literature in that it systematically documents the prenatal structural development of the human brain. It is based on lifelong study using essentially a single staining procedure, the classic rapid Golgi procedure, which ensures an unusual and desirable uniformity in the observations. The book is amply illustrated with 81 large, high-quality color photomicrographs never previously reproduced. These photomicrographs, obtained at 6, 7, 11, 15, 18, 20, 25, 30, 35, and 40 weeks of gestation, offer a fascinating insight into the sequential prenatal development of neurons, blood vessels, and glia in the human brain.